A Fast and Accurate Calculation Method of Line Breaking Power Flow Based on Taylor Expansion - Li, Shuaihu; Zhao, Xiang; Liang, Wenju; Hossain, Md Tanjid; Zhang, Zhidan (Frontiers in Energy Research, 2022)
In order to quickly obtain the voltage value of each node after the power system line is disconnected, a fast and accurate calculation method of breaking voltage based on Taylor series expansion is proposed in this study, which can calculate the value of nodal voltage of the system in a short time. At first, a breaking parameter is introduced into the admittance of the disconnected line, and a nonlinear disconnection function is constructed about the breaking parameter. After the line is disconnected, the voltage of each node and the admittance matrix of each node are functions of the relevant parameters, and then, the Taylor series is used to expand. The voltage of each node of the system before breaking is considered as the initial value of the Taylor series, and the first, second, and third derivatives of the node voltage with respect to the parameter are considered as the correction term; the voltage of each node of the system is calculated after the line is disconnected. Finally, the simulation results of the IEEE 14-node system are used to verify the correctness of the proposed method.